2020
DOI: 10.1021/acs.jced.0c00484
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Density Data of Three Carbon Dioxide and Oxygen Binary Mixtures at Temperatures from 276 to 416 K and at Pressures up to 20 MPa

Abstract: U min ()= 0.2 kg.m-3 U max ()= 8 kg.m-3 U min ()= 0.5 kg.m-3 U max ()= 15 kg.m-3 U min ()= 0.4 kg.m-3 U max ()= 13 kg.m-3 U min ()= 0.1 kg.m-3 U max ()= 3 kg.m-3 U min ()= 0.1 kg.m-3 U max ()= 3 kg.m-3 U min ()= 0.1 kg.m-3 U max ()= 2 kg.m-3 U min ()= 0.2 kg.m-3 U max ()= 5 kg.m-3 U min ()= 0.1kg.m-3 U max ()= 2.5 kg.m-3 p/MPa /kg.m-3 p/MPa /kg.m-3 p/MPa /kg.m-3 p/MPa /kg.m-3  p/MPa /kg.m-3  p/MPa /kg.m-3  p/MPa /kg.m-3  p/MPa /kg.m-3 

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…The complete study of these systems as well as precise solubility data tables are provided in our previous work. 6 The predictions of the VLE of the CO 2 + O 2 gas mixture calculated by the same model, which is reduced to the PR EoS (since there are no electrolytes or associative compounds), are quite good; however, this representation can be improved, especially in the region of the critical points of the mixture by using other mixing rules (see Lasala et al 29 and Ahamada et al 4 ), a multiparametric EoS (e.g., EoS-CG), or adding a crossover treatment (see Dicko and Coquelet 30 and Janecek et al 31 ). All these options add additional parameters, which is not necessary for our study, as demonstrated by the prediction results obtained for multicomponent systems (see Section 3.3).…”
Section: Thermodynamic Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The complete study of these systems as well as precise solubility data tables are provided in our previous work. 6 The predictions of the VLE of the CO 2 + O 2 gas mixture calculated by the same model, which is reduced to the PR EoS (since there are no electrolytes or associative compounds), are quite good; however, this representation can be improved, especially in the region of the critical points of the mixture by using other mixing rules (see Lasala et al 29 and Ahamada et al 4 ), a multiparametric EoS (e.g., EoS-CG), or adding a crossover treatment (see Dicko and Coquelet 30 and Janecek et al 31 ). All these options add additional parameters, which is not necessary for our study, as demonstrated by the prediction results obtained for multicomponent systems (see Section 3.3).…”
Section: Thermodynamic Modelingmentioning
confidence: 99%
“…In addition, important properties to be studied for such storage applications include gas density and viscosity, its solubility in brine, and gas hydrate stability curves. In our recent work, we have studied the density of the CO 2 + O 2 mixture and the solubility of CO 2 , , O 2 , and H 2 in brine under underground storage conditions. Herein, in the continuity of the previous work, we are interested in the study of the dissociation points of the hydrates of CO 2 , O 2 , and their mixtures under transport and storage conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For the design of power plants based on the Allam cycle, information on the thermal and caloric properties as well as phase equilibria of the working fluid is needed. The interest in the Allam cycle has led to a number of experimental studies of thermophysical properties of mixtures relevant for the Allam cycle in recent years [4][5][6][7][8][9][10] that can be used as basis for the thermodynamic modeling by equations of state (EOS). In principle, EOS can be used to predict mixture properties from pure component properties using predictive mixing and combination rules.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the findings reported in the literature give no clear picture, which EOS to use for modeling mixture properties of CO 2 + O 2 . Furthermore, a significant amount of new data has become available only recently and was not included in most studies discussed above [4][5][6][7][8][9][10]. Therefore, in this work, we have studied the modeling of mixture properties of CO 2 + O 2 using different EOS.…”
Section: Introductionmentioning
confidence: 99%